Videotext Over Mall Elevate Reading Fluency for Remote Area’s Intensive Program University Student - Hasanah, Shofiyatul; Pradipta, Parahita; Efendi, Erfan (FKIP Universitas Lampung, 2022)
The objectives of study were meant to perceive the impact of videotext on reading fluency over MALL in remote area student. Nonetheless, the writing is moderately simulating the concurrences with the impacts of videotext, drained of any current methodology investigating the impacts of videotext as a part to small participants reading intercessions. Methods were quasi-experimental, non-randomized pre-test and post-test design with 60 students over remote areas and interview case study plan as testimonial with six pseudonyms contributors. along with comparation of two intercession correspondences to one another. Well-separated of all participants scores mark. Findings demonstrated moderate to effective impacts for the two intercessions across all members, with little distinction betwixt the two instruments. Conclusion the established hypothesis has been accepted. Keywords: videotext, mobile assisted language learning, reading fluency, remote area.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202225